Convergence of the spectral decomposition of a function from the class W_p,m^1 (G), p > 1, in the vector eigenfunctions of a differential operator of the third order - Abbasova, Yu. G.; Kurbanov, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We consider, a third-order differential operator with matrix coefficients. The absolute and uniform convergence of the orthogonal expansion of a vector function from the class W_p,m^1 (G), p > 1, in the vector eigenfunctions of this operator is studied and the rate of uniform convergence of this expansion on G = [0, 1] is estimated.